2011
DOI: 10.1039/c0gc00330a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of efficient anti-Markovnikov olefin hydroarylation catalyzed by homogeneous Ir(iii) complexes

Abstract: The mechanism of the hydroarylation reaction between unactivated olefins (ethylene, propylene, and styrene) and benzene catalyzed by [(R)Ir(m-acac-O,O,C 3 )-(acac-O,O) 2 ] 2 and [R-Ir(acac-O,O) 2 (L)] (R = acetylacetonato, CH 3 , CH 2 CH 3 , Ph, or CH 2 CH 2 Ph, and L = H 2 O or pyridine) Ir(III) complexes was studied by experimental methods. The system is selective for generating the anti-Markovnikov product of linear alkylarenes (61 : 39 for benzene + propylene and 98 : 2 for benzene + styrene). The reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 86 publications
2
24
0
1
Order By: Relevance
“…[165] As eries of mechanistic studies were also reported, including DFT calculations and organometallic studies,which highlighted aC ÀHactivation mechanism based on an iridium(III)-alkyl-mediated concerted metalationdeprotonation (CMD) pathway. [166] Besides iridium(III) catalysts,t he use of well-defined ruthenium(II) catalysts was described almost simultaneously. Indeed, Gunnoe first reported in 2003 the use of ah ydridotris(pyrazolyl)borate-derived ruthenium complex for the direct alkylation of benzene with ethylene (51 turnovers after 4h)o rp ropene (14 turnovers after 19 h) with a1 .6:1.0 ratio of n-propyl-versus isopropylbenzene in the latter case (Scheme 61).…”
Section: Alkylation With Alkenesmentioning
confidence: 99%
“…[165] As eries of mechanistic studies were also reported, including DFT calculations and organometallic studies,which highlighted aC ÀHactivation mechanism based on an iridium(III)-alkyl-mediated concerted metalationdeprotonation (CMD) pathway. [166] Besides iridium(III) catalysts,t he use of well-defined ruthenium(II) catalysts was described almost simultaneously. Indeed, Gunnoe first reported in 2003 the use of ah ydridotris(pyrazolyl)borate-derived ruthenium complex for the direct alkylation of benzene with ethylene (51 turnovers after 4h)o rp ropene (14 turnovers after 19 h) with a1 .6:1.0 ratio of n-propyl-versus isopropylbenzene in the latter case (Scheme 61).…”
Section: Alkylation With Alkenesmentioning
confidence: 99%
“…In addition to BTX, there is also a high demand for n-alkyl arenes, which are precursors for surfactants with high detersive power [128]. Synthesis of n-alkyl arenes requires the challenging anti-Markovnikov arylation of olefins [129][130][131], and hence branched alkyl arenes synthesized via FriedelÀCrafts alkylation currently dominate the surfactant industry. Goldman and Brookhart have reported an efficient route to n-alkyl arenes directly from n-alkane as starting materials via dehydroaromatization reaction (14) [61].…”
Section: Aromatics Via Alkyl Group Cross Metathesis and Alkane Cyclodmentioning
confidence: 99%
“… [14,16–20] These potential advantages include: a) direct arene alkenylation (rather than alkylation) via β‐hydride elimination after the olefin insertion step, b) selective production of 1‐aryl alkane/alkene by circumventing carbocationic intermediates that lead to Markovnikov selectivity, c) conversion of electron‐deficient arenes, d) new regioselectivity for alkenylation or alkylation of substituted arenes, and e) inhibition of polyalkylation since alkylated or alkenylated products can be less reactive than starting arenes [14] . Molecular catalysts involving Ni, Ir, Ru, Pt, Pd and Rh have been studied for catalytic C−H alkylation or alkenylation of arenes with α‐olefins [15,16,21–35] …”
Section: Introductionmentioning
confidence: 99%
“…[14] Molecular catalysts involving Ni, Ir, Ru, Pt, Pd and Rh have been studied for catalytic CÀ H alkylation or alkenylation of arenes with α-olefins. [15,16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Recently, we reported Rh-catalyzed arene alkenylation to directly synthesize styrene and 1-aryl alkenes using molecular catalysts in homogeneous processes. [13,14,[36][37][38][39][40][41] Based on the mechanistic studies, our initial proposed catalytic cycle involves (Scheme 3): a) Rh-carboxylate assisted arene CÀ H activation, b) ethylene coordination and insertion into a Rh-aryl bond, c) βhydride elimination, and d) alkenyl arene dissociation and oxidation of a RhÀ H intermediate with CuX 2 (X = carboxylate) to regenerate the starting catalyst.…”
Section: Introductionmentioning
confidence: 99%